The Potential for a Conditional Cash Transfer Program in Addis Ababa, Ethiopia to Impact Maternal and Child Nutrition: An Exploration of Facilitating and Limiting Factors (P10-148-19). (13th June 2019) - Woldegebreal, Demewoz; Vosti, Stephen; Engle-Stone, Reina
Abstract: Objectives: To identify facilitating and limiting factors that could affect the potential impacts on maternal and child nutrition of the Ethiopian urban conditional cash transfer program. Methods: An exploratory qualitative study was conducted among the beneficiaries of the Ethiopian urban conditional cash transfer program (urban Productive Safety Net Program, urban PSNP) and key informants (program administrators and stakeholders). Eight focus group discussions (FGD), seven in-depth interviews, and eleven key informant interviews were conducted in five sub-cities of Addis Ababa. Coding was facilitated by NVivo 12 software. Results: A substantial number of pregnant, lactating, and women with children under five years of age are beneficiaries of the urban PSNP. Beneficiaries reported that the majority of the money received from the program was spent on food (mostly on staples) and rent. FGD participants and key informants believed that the amount of cash provided by the PSNP program was too small to improve maternal and child nutrition. The conditional urban PSNP involves working an assigned job and beneficiaries are required to save 20% of the cash from the PSNP program, but no nutrition-specific conditions are imposed. Household barriers identified by interviewees included: low autonomy among women to use the cash transferred, and the size of the cash transfer (based on a family of 4) relative to actual family size. Programmatic facilitating factors were: existing national nutrition initiatives (National Nutrition program) that could be linked with the urban PSNP, urban PSNP organizational structure (i.e., the existence of urban PSNP peer support groups) initiatives to engage the PSNP beneficiaries in nutrition-sensitive jobs (e.g., urban agriculture), and targeting the cash transfer to poor households having a child under five years of age. Conclusions: If strengthened and modified, the urban PSNP has the potential to improve maternal and child nutrition in Ethiopia. This impact can be strengthened by collaborating with ongoing and planned nutrition programs (e.g., Ministry of Health). Further study of the effects and cost-effectiveness of including alternative maternal and child nutrition programs in the current urban PSNP is recommended. Funding Sources: UC Davis Blum Center for Developing Economies and the Bill & Melinda Gates Foundation.